The effect of indigenous and exogeneous endophythic bacteria on shoot production, soil and tea leaf nitrogen content under drought season - Pranoto, Eko (Jurnal Penelitian Teh dan Kina, 2014)
Drought season with rainfall <100 mm/month for more than two months cause tea plant growth disturbed, reduction in leaf production, and death of plant. Nitrogen was the macro essential nutrient needed for vegetative growth and was important for building the cell, include protein, DNA, and RNA. Nitrogen was related on proline content to support the drought tolerance in plant. The nitrogen requirement on tea plantation can be fulfilled by anorganic, organic, and biofertilizer. This study was aimed at determining effect of indigenous and exogeneous endophythic bacteria effectiveness on productivity and nitrogen content on soil and tea plant. This research was carried out at the Block A7 Gambung, Research Intitute for Tea and Cinchona. The study was conducted during drought season (June to September 2013). The experimental design was randomize blocked design with factorial arrangement and three levels of each factor: i.e. 1. anorganic nitrogen dose (N): a. 100% N dose; b. 75% N dose; c. 50% N dose, 2. endophytic bacteria (E); a. control (without); b. indigenous (DtG7-5); c. exogenous (Acinetobacter sp). The result showed that the indigenous and exogenous endophytic bacteria could be maintained the leaf production and significantly different on drought season, i.e. on 3rd, 4th, and 6th plucking. The highest leaf production increasing depend on before applied the treatment was the combined of endophitic bacteria and 100% anorganic fertilizer. All of the treatment has not significantly different on N-total of soil and N content of plant. The applied of indigenous and also exogenous endophytic bacteria was produced the average of nitrogen content on soil around 10-13% higher than the control treatment (only anorganic fertilizer applied) and the nitrogen content on plant was lower 1-2% than control treatment (only anorganic fertilizer applied).